Phylogenetics, character evolution, and distribution patterns of the greenbriers, Smilacaceae (Liliales), a near‐cosmopolitan family of monocots. (29th October 2013) - Qi, Zhechen; Cameron, Kenneth M.; Li, Pan; Zhao, Yunpeng; Chen, Shichao; Chen, Guangcun; Fu, Chengxin
<x xml:space="preserve">Abstract</x> Smilacaceae, composed of Smilax and Heterosmilax, are a cosmopolitan family of > 200 species of mostly climbing monocots with alternate leaves characterized by reticulate venation, a pair of petiolar tendrils and usually prickly stems. Although there has been a long history of studying Smilax since Linnaeus named the genus in 1753, the phylogenetic history of this dioecious family remains unclear. Here we present results based on nuclear ribosomal internal transcribed spacer (nrITS) and plastid matK and rpl16 intron DNA sequence data from 125 taxa of Smilacaceae. Our taxon sampling covers all sections of Smilax and Heterosmilax and major distribution zones of the family; species from Ripogonaceae and Philesiaceae are used as outgroups. Our molecular analysis indicates that phylogenetic relationships largely contradict the traditional morphological classification of the family, instead showing a conspicuous geographical pattern among the species clades. The previously recognized genus Heterosmilax was found to be embedded in Smilax. Species in the family are separated into primarily New World and Old World clades, except for a single species lineage, Smilax aspera, that is sister to the remaining species of the family, but with poor statistical support. Ancestral character state reconstructions and examination of distribution patterns among the clades provide important information for future taxonomic revisions and historical biogeography of the group. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 535–548.